The Funding Issues With The Concept of Interest and The Implementation of Mudharabah Contracts in Islamic Banking Funding Systems - Amriatus Safa’ah; Audy Putri Adinda; Bintan Muara Zahra (Mabadi Iqtishad Al Islami, 2024)
Mudharabah contract is a lending agreement conducted within banks with a profit-sharing scheme. In this case, the Mudharabah contract is regulated in the DSN-MUI fatwa which has several aspects of rules in the implementation of Mudharabah contracts as funding or loans. This research is a literature analysis conducted and observed through examination, review, discussion of classic and modern literature as well as analysis using existing data. Data collection is carried out using documentation methods from various papers, articles, books, and journals. Then analyzed using content analysis and quantitative analysis methods, by analyzing descriptive or scientific data. The results of this study are explanations regarding Mudharabah, implementation, and contemporary issues. The similarity of this research with other studies is discussing Mudharabah, implementation, and contemporary issues, while the difference is that this paper provides discussions that have been studied from the thoughts of the authors based on what the authors obtained from papers, articles, books, and journals that already exist and adjust the implementation of Mudharabah contracts based on Majelis Ulama Indonesia.